Risk factors in the mother-child relationship that predispose to the development of early childhood caries - Moimaz, S. A. S. [UNESP]; Garbin, A. J. Í.; Lima, A. M. C.; Lolli, L. F.; Saliba, O.; Garbin, C. A. S. (European Archives Of Paediatric Dentistry : Official Journal Of The European Academy Of Paediatric Dentistry, 2014)
This study focused on the risk factors in mother-child relationship that predispose babies to the development of dental caries. A prospective cohort study with 80 mother-child pairs was conducted. The mothers responded at 12, 18 and 30 months after their children's birth, to questions about variables related to diet, sucking habits, and oral care. Children were clinically examined to verify caries lesions (white spot lesions or cavitation). Data were analysed using Chi squared or Fisher's exact tests. The significance level was set at 5 %. Of the total, 3.75 % showed cavitated lesions after 18 months; 6.25 and 45 % had spot white lesions, respectively, at 18 and 30 months. The cariogenic diet was high at 12 (63.75 %) and 30 (88.75 %) months. Good oral hygiene was present in a minority of children at 12 months (46.25 %), but increased at 30 months (65 %), helping to prevent cavities and white spot lesions over this period (p = 0.0005). The variables of the blocks sucking habits and diet were not associated with caries. The lack of oral care in children was a risk factor for dental caries development.
Keywords: Mother–child relations; Dental caries; Oral hygiene; Diet Cariogenic; Breast feeding; Longitudinal studies